Financing for Accountability: A Multi Site Analysis of Islamic Governance–Driven Budget Practices in Private Islamic Higher Education Institutions - Siti Nurhasanah Yahya; Mulyawan Safwandy Nugraha; Deni Melyati; Elvita Sitna Hajar; Mamah Siti Rohmah; Satria Adi Pradana (Badan Litbang dan Diklat Kementerian Agama RI, 2025)
This study investigates how educational financing practices influence managerial accountability in Private Islamic Higher Education Institutions (PIHEI). Although financing and accountability have been widely discussed in higher education, limited research has explored how financing systems specifically shape accountability within PIHEI, particularly in relation to Islamic governance values. This study addresses this gap by analyzing the extent to which financing sources, allocation patterns, and evaluation mechanisms contribute to strengthening managerial accountability. A qualitative multi site case study was conducted across 30 PIHEI involving 123 informants. Data were collected through questionnaires and semi structured interviews, and analyzed using descriptive techniques and thematic analysis to identify patterns in financing practices and accountability processes. The findings indicate that, first, PIHEI remains highly dependent on student tuition fees, while access to government and community funding is limited due to administrative barriers and accreditation requirements. Second, budget allocation is concentrated on basic operational needs, with insufficient support for research, community service, and institutional development. Third, financing evaluations related to adequacy, efficiency, equity, and cost effectiveness are not consistently implemented, weakening accountability mechanisms. These findings highlight the need for financing diversification, improved reporting systems, and stronger alignment with Islamic governance principles. The study concludes by recommending performance-based funding support and institutional capacity building to enhance financial sustainability and managerial accountability in PIHEI. ABSTRAK Penelitian ini mengkaji bagaimana praktik pembiayaan pendidikan memengaruhi akuntabilitas manajerial pada Perguruan Tinggi Keagamaan Islam Swasta (PTKIS). Meskipun isu pembiayaan dan akuntabilitas telah banyak dibahas dalam konteks pendidikan tinggi, masih sedikit penelitian yang menelaah bagaimana sistem pembiayaan secara spesifik membentuk akuntabilitas di PTKIS, terutama terkait penerapan nilai‑nilai tata kelola Islam. Studi ini mengisi kesenjangan tersebut dengan menganalisis sejauh mana sumber pembiayaan, pola alokasi anggaran, dan mekanisme evaluasi berkontribusi dalam memperkuat akuntabilitas manajerial. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi multi‑lokasi pada 30 PTKIS dan melibatkan 123 informan. Data dikumpulkan melalui kuesioner dan wawancara semi‑terstruktur, kemudian dianalisis menggunakan teknik deskriptif dan analisis tematik untuk mengidentifikasi pola dalam praktik pembiayaan dan proses akuntabilitas. Hasil penelitian menunjukkan tiga temuan utama. Pertama, PTKIS masih sangat bergantung pada biaya kuliah mahasiswa, sementara akses terhadap pendanaan pemerintah dan masyarakat terbatas akibat hambatan administratif dan persyaratan akreditasi. Kedua, alokasi anggaran lebih banyak difokuskan pada kebutuhan operasional dasar, dengan dukungan yang minim untuk penelitian, pengabdian kepada masyarakat, dan pengembangan kelembagaan. Ketiga, evaluasi pembiayaan terkait kecukupan, efisiensi, pemerataan, dan efektivitas biaya belum diterapkan secara konsisten sehingga melemahkan mekanisme akuntabilitas.